2017
DOI: 10.1038/s41598-017-14204-3
|View full text |Cite
|
Sign up to set email alerts
|

CSF tau is associated with impaired cortical plasticity, cognitive decline and astrocyte survival only in APOE4-positive Alzheimer’s disease

Abstract: In Alzheimer’s disease (AD) patients, apopoliprotein (APOE) polymorphism is the main genetic factor associated with more aggressive clinical course. However, the interaction between cerebrospinal fluid (CSF) tau protein levels and APOE genotype has been scarcely investigated. A possible key mechanism invokes the dysfunction of synaptic plasticity. We investigated how CSF tau interacts with APOE genotype in AD patients. We firstly explored whether CSF tau levels and APOE genotype influence disease progression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 62 publications
2
40
0
Order By: Relevance
“…Recent studies illustrated that after changing the neuron structure of human ApoE4 , the signs of AD were eliminated, and cell function and viability were improved [ 29 ]. In AD patients with ApoE4 , the higher the tau level in cerebrospinal fluid (CSF), the worse the plasticity of long-term potentiation- (LTP-) like cortical, and the faster the disease progression [ 30 ]. The reduction of ApoE suggested that cordycepin might affect the formation of NFTs and A β , reduce the tau level in CSF, and restore the plasticity of LTP-like cortical.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies illustrated that after changing the neuron structure of human ApoE4 , the signs of AD were eliminated, and cell function and viability were improved [ 29 ]. In AD patients with ApoE4 , the higher the tau level in cerebrospinal fluid (CSF), the worse the plasticity of long-term potentiation- (LTP-) like cortical, and the faster the disease progression [ 30 ]. The reduction of ApoE suggested that cordycepin might affect the formation of NFTs and A β , reduce the tau level in CSF, and restore the plasticity of LTP-like cortical.…”
Section: Discussionmentioning
confidence: 99%
“…While there is consistent evidence of a diminished motor cortical plasticity response in schizophrenia, very little is known about its specificity to schizophrenia. Indeed, cortical plasticity has been systematically evaluated and found to be abnormal in individuals with depression (Kuhn et al, 2016), autism (Oberman et al, 2016;Pedapati et al, 2016), Alzheimer's dementia (Koch et al, 2017). However, there are no head-to-head comparisons of how cortical plasticity varies across these diverse psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons expressing P301S tau are less viable when co-cultured with APOE4-expressing glia compared to APOE2- or APOE3-expressing glia, while co-culture with APOE −/− glia leads to the greatest neuronal viability, supporting the idea that APOE4 represents a toxic gain-of-function (Shi et al, 2017). Higher CSF tau levels are associated with faster disease progression and reduced cortical plasticity in patients, but only in APOE4 carriers (Koch et al, 2017), further cementing a role for APOE4 in exacerbating tau pathology. Since some evidence suggests that APOE can be expressed by neurons under stress (Xu et al, 1998, 2006; Harris et al, 2004), it is possible that neuron-derived APOE4 directly mediates tau toxicity in neurons, but the above data suggests that glia-derived APOE4 is likely contributing as well.…”
Section: Overview Of Apoe Isoformsmentioning
confidence: 99%